Corporate Governance and Accounting Information Quality： Empirical Investigation from China - Yang, Pei (2022)
This thesis uses empirical analysis to examine the impact of corporate governance on the accounting information quality in China. Board size, board independence, CEO duality, and state ownership are proxy variables for corporate governance, and audit report timeliness is a proxy variable for accounting information quality. OLS regression models are then applied to investigate the connection between the proxy variables of the firm and the proxy variables of accounting information quality. The research does not find a significant correlation between board size, board independence, CEO duality, and accounting information quality. However, State ownership is positively and significantly related to accounting information quality. To ensure the robustness of this result, this research changed the explanatory variable of state ownership and did a new regression analysis. Overall, the results are similar to the first regression analysis.